The state of readiness of the interior design industry in the adoption of building information modelling in Malaysia - Abd. Hamid, Abu Bakar (2020)
Building Information Modelling (BIM) is a radically emerging technology approach for design, construction and facility management that is capable of facilitating building design and construction more efficiently. This work aims to assess the effectiveness of BIM implementation for interior design firms by looking at the opportunities and barriers involved. Is it practical for BIM to deal with implementation problems and improve work overall process efficiency? Or can it improve design knowledge and technology in interior design firms? The implementation of BIM in the interior design industry remains behind, as compared to other building professions. Preliminary studies demonstrate that lack of knowledge about BIM is among the reasons as to why interior design firms do not implement BIM technology. Hence, there is a vital need to identify why BIM technology is not implemented by interior design firms. The purpose of this work is to identify methods to improve the implementation of BIM in the interior design industry. The primary objective is to develop a conceptual framework for the implementation of BIM technology in the interior design firm. The methodology involves applying descriptive survey methods such as structured questionnaires and interviews for selected interior design firms. The study was conducted at 63 interior design firms located around the Klang Valley in Malaysia, which were selected by using three groups, namely, small, medium and large. Two methods of data were collected, namely, quantitative data (questionnaire) and qualitative data (interview). Data from the questionnaire was used to determine potential factors and barriers to BIM implementation, while the interview data describes in detail the questionnaire data. The findings reveal that the knowledge and costs implementation are the primary barriers as to why the interior design firms do not implement BIM. Additionally, technology and human resources are also barriers that are faced when implementing BIM in interior design firms. The study also found that large interior design firms do not face many barriers in the implementation of BIM, while small interior design firms face problems in the application of BIM. Subsequently, on the basis of quantitative and qualitative data, a conceptual framework was developed to increase the application of BIM in interior design firms. This framework was discussed and verified with interior design experts, and is intended to act as a guideline for the interior design industry in increasing the implementation of BIM. This study is crucial, as research on the implementation of BIM in the interior design industry is still lacking, and needs to be improved by reducing the identified barrier factors.